G276(P) Impact of a regional paediatric tuberculosis network. (25th October 2020) - Sinha, A; Dixon, S; Turnbull, L; Child, F
Abstract : Introduction: Tuberculosis (TB) incidence in England and Wales has fallen by 44% since 2011 with England now classed as a low incidence area. This means that individual clinicians are seeing fewer cases of TB and experience is falling. Working with public health and the TB Control Board we have created a regional paediatric TB network consisting of tertiary and secondary TB teams across an area with varying TB incidence. The aim of this network was to improve and standardise care, reduce diagnostic delay and increase our shared experience. Method: The network has been commissioned for and encourages engagement and referrals from DGH paediatricians and TB nurses. It includes a weekly virtual TB clinic and enhanced Paediatric annual cohort audit with feedback of learning points at regular stakeholder education days. Results: The network and virtual clinic have been running for 5 and 2 years respectively. Seventy patients have been discussed at the virtual clinic: in 57% of children this led to a change to investigation, diagnosis or management. Four children had a change of diagnosis from latent TB infection (LTBI) to active disease. The clinic has been able to cover gaps in service supporting solo clinicians and TB nurses and enabling 53% of children to have their care closer to home. Service delivery issues such as adult physicians looking after children without paediatric input and failure to provide adequate chemoprophylaxis in high risk children have been identified and addressed. Reasons for diagnostic delay have been identified to be different in different areas allowing site appropriate solutions to be explored. Focussed education sessions on safeguarding, pharmacy and drug delivery have been provided. Communication has improved region-wide and experience is increasing. Conclusion: The TB network has been well received by TB teams across the region. It is a great example of collaborative working, enabling resolution of service issues and improved quality of care for our patients.